A magnetic-spring-based, low-frequency-vibration energy harvester comprising a dual Halbach array. (9th August 2016) - Salauddin, M; Halim, M A; Park, J Y
Abstract: Energy harvesting that uses low-frequency vibrations is attractive due to the availability of such vibrations throughout the ambient environment. Significant power generation at low-frequency vibrations, however, is challenging because the power flow decreases as the frequency decreases; moreover, designing a spring-mass system that is suitable for low-frequency-vibration energy harvesting is difficult. In this work, our proposed device overcomes both of these challenges by using a dual Halbach array and magnetic springs. Each Halbach array concentrates the magnetic-flux lines on one side of the array while suppressing the flux lines on the other side; therefore, a dual Halbach array allows for an interaction between the concentrated magnetic-flux lines and the same coil so that the maximum flux linkage occurs. During the experiment, vibration was applied in a horizontal direction to reduce the gravity effect on the Halbach-array structure. To achieve an increased power generation at low-amplitude and low-frequency vibrations, the magnetic structure of the dual Halbach array and the magnetic springs were optimized in terms of the operating frequency and the power density; subsequently, a prototype was fabricated and tested. The prototype device offers a normalized power density of 133.45 μ W cm −3 g −2 that is much higher than those of recently reported electromagnetic energy harvesters; furthermore, it is capable of delivering a maximum average power of 1093 μ W to a 44 Ω optimum load, at an 11 Hz resonant frequency and under a 0.5 g acceleration.